2006
DOI: 10.1002/ijc.22165
|View full text |Cite
|
Sign up to set email alerts
|

Deriving evolutionary tree models of the oncogenesis of endometrial adenocarcinoma

Abstract: Endometrial adenocarcinoma (EAC) is the fourth leading cause of cancer death in women worldwide, but not much is known about the underlying genetic factors involved in the development of this complex disease. In the present work, we used 3 different algorithms to derive tree models of EAC oncogenesis from data on the frequencies of genomic alterations in rat chromosome 10 (RNO10). The tumor material was derived from progenies of crosses between the EAC susceptible BDII inbred rat strain and two non susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Cytogenetic and molecular analysis of ECs developed in a rat model for this malignancy revealed frequent allelic losses/deletions in the proximal to middle part of rat chromosome 10 (RNO10) [ 11 13 ]. Through deriving onco-tree models based on allelic imbalance (AI) data, we determined the likely order of allelic loss events along RNO10 as well as their relationship to each other [ 14 ]. In the analysis one of the small regions of recurrent allelic loss located at RNO10q24-q25 was placed closest to the root of the onco-tree models, suggesting this region to harbor early and important genetic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic and molecular analysis of ECs developed in a rat model for this malignancy revealed frequent allelic losses/deletions in the proximal to middle part of rat chromosome 10 (RNO10) [ 11 13 ]. Through deriving onco-tree models based on allelic imbalance (AI) data, we determined the likely order of allelic loss events along RNO10 as well as their relationship to each other [ 14 ]. In the analysis one of the small regions of recurrent allelic loss located at RNO10q24-q25 was placed closest to the root of the onco-tree models, suggesting this region to harbor early and important genetic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…As before, the interpretation is that a given mutation increases the chances of obtaining the following mutation. A number of studies have constructed oncogenetic trees from cross-sectional data, including for renal cell carcinoma (12), endometrial adenocarcinoma (13), gastrointestinal stromal tumors (14), oral cancer (15), and colon cancer (16). …”
Section: Introductionmentioning
confidence: 99%
“…Although no homozygous transformants were obtained, heterozygous transformants can also be to study the function of PsFP1 , because the PsFP1 gene is hardly expressed in heterozygous transformants. Previous studies have shown that allelic expression imbalance exists widely in eukaryotes [ 38 , 39 , 40 ]. Thus, the significant decrease in PsFP1 expression in heterozygous transformants may be due to the deletion of the preponderant allele of PsFP1 .…”
Section: Discussionmentioning
confidence: 99%